Stereoselective synthesis of (S)-dapoxetine starting from trans-cinnamyl alcohol - Venkatesan, K.; Srinivasan, K. V. (Arkivoc, 2008)
A novel stereoselective synthesis of (S)-dapoxetine starting from commercially available trans-cinnamyl alcohol is described. Sharpless Asymmetric Epoxidation (SAE) is utilized as the key step in this synthetic strategy.
Keywords: (S)-dapoxetine; antidepressant; Sharpless asymmetric epoxidation; stereoselective synthesis